Aggregation behavior of hydrophobically modified dextran in aqueous solution: a fluorescence probe study - Vieira, NAB; Moscardini, M. S.; Tiera, VAD; Tiera, M. J. (Elsevier B.V., 2003)
Dextrans (M-W = 11.000 and M-w = 40.000) have been modified with 4-hexyl benzoyl chloride and their aggregation behavior was studied in aqueous solution employing the fluorescent probes pyrene and 1,8 anilinonaphtalene sulfonic acid sodium salt (1,8 ANS). The photophysical studies showed that above a critical concentration the derivatives tend to form aggregates having different properties, which depend on both the degree of substitution (alpha) and the molecular weight of the sample. The parameter alpha has a marked effect on the critical aggregation concentrations (CAC) and aggregate proper-ties. Hydrophobic microenvironments can be detected for substituted dextrans having alpha values varying from 0.01 to 0.19. CAC values decreased by two orders and magnitude when the molecular weight increased from 11 to 40 kDa, leading to formation of more apolar aggregates and diminishing by about 30% the polarity of the microenviromnents. Pre-aggregation was evidenced by pyrene excimer emission and intermolecular interactions were responsible by the formation of aggregates leading to solution behaviour similar to that of common surfactants. (C) 2003 Elsevier B.V. Ltd. All rights reserved.
Keywords: dextran; hydrophobically modified; fluorescence probe technique; critical aggregation concentration; micropolarity